Enforcement Design in EU Digital Regulation: Lessons for the Digital Fairness Act - Zoboli, Laura; Mazur, Joanna (Cambridge University Press, 2026)
While the legislative text of the Digital Fairness Act (DFA) has not yet been published, it is already clear that its effectiveness will depend as much on its enforcement design as on the content of its substantive provisions. Experience with recent instruments – including the Digital Services Act, the Digital Markets Act, the Artificial Intelligence Act and the Data Act – reveals persistent difficulties in ensuring consistent and timely enforcement across Member States. Building on the findings of the Commission’s Fitness Check of EU Consumer Law on Digital Fairness, this article examines how the enforcement design developed in these legal acts can inform the institutional and procedural design of the DFA. It argues that the challenges identified by the Digital Fitness Check reflect deeper patterns of procedural, institutional and epistemic fragmentation in EU enforcement. By analysing how different enforcement designs address these tensions through mechanisms of centralisation, coordination and capacity-building, the article identifies key design choices that may shape the emerging enforcement framework of the DFA.
Keywords: 56 Ciencias Jurídicas y Derecho::5603 Derecho internacional; ODS 16 - Paz, justicia e instituciones sólidas; Digital Fairness Act; Digital regulation; Enforcement design